2016
DOI: 10.1016/j.gie.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Peroral endoscopic myotomy in the endoscopy unit: location, location, location

Abstract: openAccessArticle: Falsecover date: 2016-01-01pii: S0016-5107(15)02745-5Harvest Date: 2016-01-06 13:07:34issueName:Page Range: 126-126href scidir: http://www.sciencedirect.com/science/article/pii/S0016510715027455pubType: Original articleClinical endoscopy: Editoria

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It has been proposed that POEM may be associated with cost savings considering its less invasive nature, which translates into shorter procedural times and easier post-procedural care. In addition, POEM is typically performed in the endoscopy unit[11819] rather than operating theater, with the latter entailing higher charges. However, it must be acknowledged that RHM is performed with a fundoplication as opposed to POEM which does not.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that POEM may be associated with cost savings considering its less invasive nature, which translates into shorter procedural times and easier post-procedural care. In addition, POEM is typically performed in the endoscopy unit[11819] rather than operating theater, with the latter entailing higher charges. However, it must be acknowledged that RHM is performed with a fundoplication as opposed to POEM which does not.…”
Section: Discussionmentioning
confidence: 99%
“…However, some conditions must be met. Pannu et al [48] suggested that preparation of the following before performing POEM in an endoscopic unit is essential: (1) stateof- the-art facilities, (2) general anesthesia equipment in the endoscopy unit, (3) full anesthesia support team with protocol of anesthesia for POEM, (4) Considering surgical back-up. On the other hand, no anesthetic guidelines have been established for POEM and anesthetic management is inadequate.…”
Section: Future Of Anesthetic Management For Poemmentioning
confidence: 99%